Development of Digital Infographic Based on Housefly Exoskeleton Bacterial Identification - Lulu Ulfah Audriansyah; Firdaus Daud; Syamsiah Syamsiah; Ismail; Alimuddin Ali (Postgraduate, University of Mataram, 2025)
Digital infographics can be an alternative visual learning media that can be used both inside and outside the classroom. Content related to bacteria in relevant learning media is very important, as bacteria can be found almost everywhere, including on the exoskeletons of houseflies. Therefore, the aim of this study is to develop a digital infographic based on the identification of bacteria on the exoskeletons of houseflies using the ADDIE development model. Product validation was carried out by 3 experts, and implementation was conducted with 32 tenth-grade students at SMAN 20 in Gowa Regency. This digital Eubacteria infographic is a visual representation of research conducted in the FMIPA UNM laboratory. It illustrates six different types of bacteria identified from the exoskeleton of houseflies, complete with microscopic images and a brief description of each bacterium's characteristics. The infographic is packaged as an application accessible via Android smartphones. The results of the study show that the digital infographic was rated as very valid with an average score of 94%, very practical with an average score of 96%, and highly effective with an N-gain value of 0.8. This study indicates that the use of contextual learning media can improve students' learning outcomes.